Pemodelan Sistem Informasi Pemesanan Jasa Laundry Berbasis Android - Sitanggang, Andri Sahata; Tarisa, Pasha Adelia; Oktaviani, Tantri Indah; Khawarizmi, Abdul Hakim Al; Ferdiansyah, Rofi; Yudha, Muhammad Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Laundry services have become one of the basic needs of society in the current digital era. However, behind the process that looks simple, laundry officers face various obstacles such as unstructured order recording, delays in washing and delivery due to confusing queues. Thus the need for computer-based information is especially needed, one of which is to smoothly conduct business, especially in the laundry management information system. This article aims to analyze the laundry business process to identify the point of what problems often occur in the field. The development method used is the System Development Life Cycle (SDLC) with the Waterfall model, from the model has several stages that must be done such as collecting Data and Designing / Modeling systems using Business Process Modeling and Notation (BPMN) tools for business laundry management, it improves the work process to be more systematic and improves services such as recording, receiving, and organizing in washing.